Professionals and Public-Good Capabilities - Walker, Melanie; McLean, Monica (Critical Studies in Teaching and Learning, 2023)
Martha Nussbaum (2011) reminds us that, all over the world people are struggling for a life that is  fully  human -a  life  worthy  of  human  dignity.  Purely  income-based  and  preference-based  evaluations,  as  Sen  (1999)  argues,  do  not  adequately  capture  what  it  means  for  each person  to  have  quality  of  life.  There  are  other  things  that  make  life  good  for  a  person, including access to publicly provided professional services. The question then is what version of   education   inflects   more   towards   the   intrinsic   and   transformational   possibilities   of professional  work  and  contributions  to  decent  societies?  This paper suggests  that  we  need  a normative approach to professional education and professionalism; it is not the case that any old  version  will  do.  We  also  need  normative  criteria  to  move  beyond  social  critique  and  to overcome  a  merely  defensive  attitude  and  to  give  a  positive  definition  to  the  potential achievements  of  the  professions.  Moreover  universities  are  connected  to  society,  most especially through the professionals they educate; it is reasonable in our contemporary world to educate professional graduates to be in a position to alleviate inequalities, and to have the knowledge, skills and values to be able to do so. To make this case, we draw on the human capabilities  approach  of  Sen  (1999,  2009)  and  Nussbaum  (2000,  2011)  to  conceptualise professional  education  for  the  public  good  as  an  ally  of  the  struggles  of  people  living  in poverty and experiencing inequalities, expanding the well-being of people to be and to do in ways they have reason to value –to be mobile, cared for, respected, and so on. In particular we  are interested  in  which  human  capabilities  and  functioning’s  are  most  needed  for  a professional practice and professionalism that can contribute to transformative social change and how professional development is enabled via pedagogical arrangements